Computational Intelligence and Intelligent Systems 5th International Symposium, ISICA 2010, Wuhan, China, October 22-24, 2010. Proceedings - Cai, Zhihua; Tong, Hengjian; Kang, Zhuo.; Liu, Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 5th International Symposium on Computational Intelligence and Intelligent Systems held in Wuhan, China, in October 2010.
Section I: Evolutionary Design -- A Concurrent-Hybrid Evolutionary Algorithm for Geometric Constraint Solving -- A New DEBP Algorithm and Its Application for Hematite Content Prediction -- Multi-resource Balanced Scheduling Optimization Based on Self-adaptive Genetic Algorithm -- Space-Time Variation Operator Set in Possibility Construction Space -- The Comparison and Analysis of GP, GEP and GEP_EDA in Modeling System -- Section II: Evolutionary Optimization -- A Multi-objective Optimization Evolutionary Algorithm with Better Performances on Multiple Indicators -- A New Evolutionary Algorithms for Global Numerical Optimization Based on Ito Process -- A New Multi-objective Optimization Evolutionary Algorithm Based on Geometrical Pareto Selection and Double Neighbored Crossover -- Measurements in Fast Evolutionary Programming -- Merging the Ranking and Selection into ITO Algorithm for Simulation Optimization -- Ranking Based Selection Genetic Algorithm for Capacity Flow Assignments -- Section III: Hybrid Algorithms -- An Efficient Genetic Algorithm for the Traveling Salesman Problem -- Constructing a Novel QoS Aggregated Model Based on KBPP -- Exploring the Effects of Lamarckian Evolution and Baldwin Effect in Differential Evolution -- Research of Spatial Data Interpolation Algorithm Based on SVR Optimization by GA -- Section IV: Intelligent Systems -- 3-D Numerical Finite Element Method of Tectonic Stress Field Simulation Based on Irregular Corner-Point Grid -- Agent-Based System Dynamic Integration Development Platform and Tools -- An Analysis of Asymmetrical Threshold Polling Systems -- Diffusion Research of Leaked Coal Gas in Steel Plants under Natural Ventilation Conditions -- Spatio-temporal Simulation of Epidemiological SIQR Model Based on the Multi-Agent System with Focus on Influenza A (H1N1) -- The Research of Virtual Organization for Intelligent Sharing Based on Open Grid Service Architecture -- Section V: Particle Swarm Optimization -- A Comparative Study of Artificial Bee Colony, Bees Algorithms and Differential Evolution on Numerical Benchmark Problems -- A Self-adaptive Immune PSO Algorithm for Constrained Optimization Problems -- Crowding-Distance-Based Multi-objective Particle Swarm Optimization -- GA-ACO in Job-Shop Schedule Problem Research -- Research on Hybrid Improved PSO Algorithm -- Section VI: Predictive Modeling -- Combined with Improved Vicent Watershed and Dynamic Particle Clustering with Connected Constraints for Image Segmentation -- Feature Synthesis Algorithm Combined with k-NN Classifier for Spectral Data Classification -- Fuzzy Pattern Recognition Based on Generalized Euclidean Weight Distance Adjoined Degree and Its Application in Forecasting Hazard of Karst Collapse -- Improved Apriori Algorithm for Mining Association Rules of Many Diseases -- Improved Text Classification Technique to Acquire Job Opportunities for Disabled Persons.
Keywords: Computer science; Computer Communication Networks; Computer software; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Pattern Recognition; Computer Communication Networks; Programming Techniques